2006
DOI: 10.1029/2006jd007635
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime aerosol characteristics at a north Indian site Kharagpur in the Indo‐Gangetic plains located at the outflow region into Bay of Bengal

Abstract: [1] Keeping the importance of aerosol characterization in the out flow regions from the Indian subcontinent in view, a campaign mode observation on aerosol physical properties was made at Indian Institute of Technology campus, Kharagpur located under the vent region in the Indo-Gangetic plains during the winter month of December 2004. The aerosol spectral optical depths and near-surface mass concentrations were high with a mean aerosol optical depth of 0.7 at 500 nm and a percent share of fine mode particle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 24 publications
(31 reference statements)
4
54
0
Order By: Relevance
“…7, the locations of high aerosol source strength are seen close to the regions where most of the thermal power plants are located. The uncertainty in the source strength computed at every point arising from the standard deviation of the MODIS AOD (∼15%) and half a day uncertainty in the assumed aerosol residence time (Jaenicke, 1980) and ∼0.5 km uncertainty in scale height (Niranjan, et al, 2006), is ∼38%. With an average emission of ∼700 kg soot and ∼85 tons SO 2 per day from each of these power plants (http://www.osc.edu/research/ archive/pcrm/emissions/thermalemissions.shtml), they contribute substantially towards the anthropogenic aerosol load in this region.…”
Section: Sources Of Aerosol Generation Over the Ganga Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…7, the locations of high aerosol source strength are seen close to the regions where most of the thermal power plants are located. The uncertainty in the source strength computed at every point arising from the standard deviation of the MODIS AOD (∼15%) and half a day uncertainty in the assumed aerosol residence time (Jaenicke, 1980) and ∼0.5 km uncertainty in scale height (Niranjan, et al, 2006), is ∼38%. With an average emission of ∼700 kg soot and ∼85 tons SO 2 per day from each of these power plants (http://www.osc.edu/research/ archive/pcrm/emissions/thermalemissions.shtml), they contribute substantially towards the anthropogenic aerosol load in this region.…”
Section: Sources Of Aerosol Generation Over the Ganga Basinmentioning
confidence: 99%
“…Vertically resolved lidar back scatter profiles over an IGP location, Kharagpur, during the LC-II, observed by Niranjan et al (2006), indicated a decreasing aerosol extinction with increasing height, with a significant contribution extending up to 1.5 to 2 km. Hence we assume an aerosol extinction vertical profile in the form…”
Section: Aerosol Continuity Equationmentioning
confidence: 99%
“…Black carbon is largely responsible for the absorption of solar radiation by the aerosols, and is nearly ubiquitously present in the pollution plumes Satheesh et al, 2002;Vinoj et al, 2004). In the pollution source regions within the Indo-Gangetic plains the black carbon component is typically 10% or higher (Niranjan et al, 2006;Ganguly et al, 2009), and although the aerosol mass concentrations decrease by dry deposition during transport, this fraction stays approximately constant during transport over the Indian Ocean ). Recently, it was shown that Asian air pollution also contains substantial quantities of "brown" carbonaceous compounds in amorphous spherules, which adds to the climate effects of the black carbon (Alexander et al, 2008).…”
Section: Radiative Forcing and Atmospheric Heatingmentioning
confidence: 99%
“…Vertical distribution of aerosol particles over the continental India have been measured in few studies only, including those carried out over the south central India (Moorthy et al, 2004;Gadhavi and Jayaraman, 2006). Long-term measurements are even sparser, even though continuous measurements of aerosol vertical distribution have been made at Visakhapatnam and Kharagpur (Niranjan et al, 2006(Niranjan et al, , 2007a. Devara et al (2008) used a mobile lidar in Pune, India, whereas Badarinath et al (2009) measured backscatter coefficient profiles (532 nm) for different conditions at Hyderabad in October 2007.…”
Section: Introductionmentioning
confidence: 99%